Update of Canadian Historical Snow Survey Data and Analysis of Snow Water Equivalent Trends, 1967–2016. Issue 2 (15th March 2019) - Brown, Ross D.; Fang, Bruno; Mudryk, Lawrence
ABSTRACT: In situ observations of snow water equivalent (SWE) from manual snow surveys and automated sensors are made at approximately 1000 sites across Canada in support of water resource planning for flood control and hydroelectricity production. These data represent an important source of information for research (e.g., validation of hydrological and climate models), for applied studies (e.g., ground snow loads), and for climate monitoring. This note describes the process to update a Canadian historical snow survey dataset to 2016 and the production of a 0.1° gridded version for research applications. Analysis of trends in SWE, snow depth (SD), and density over the 50-year period from 1967 to 2016 revealed large spatial variability in trend sign and strength, with a relatively small percentage of points showing statistically significant trends. Where SWE and SD trends were significant, they tended to be negative, which is consistent with previous investigations of snow cover changes in Canada. The results show evidence of a latitudinal dependence in SWE trends, with the largest negative trends occurring over lower latitudes, and a tendency for mainly positive trends in Arctic SWE, which is consistent with observations from Russia and climate model projections of the response of Arctic snow cover to climate warming. Arctic sites also showed evidence of an increasing trend in 1 April snowpack density of 6.6 kg m −3 per decade but little corresponding change in SD. This has potentially important consequences for the soil thermal regime because it provides a cooling influence from an increase in the snowpack effective thermal conductivity. The snow survey dataset is available from the Government of Canada Open Data portal.